The snow goose - Gallico, Paul, 1897-1976. (Mattituck, N.Y. : Amereon House, 2000)
A snow goose makes repeated flights from her home in an English marsh to the beaches of Dunkirk, where she seems to escort a man in a small boat who is rescuing soldiers trapped on the beach.
Wilson's Fiction.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: Geese -- Fiction; World War, 1939-1945 -- Fiction; Geese -- Fiction; War stories; World War, 1939-1945 -- Fiction